Translocation of natural microflora from muscle surface to interior by blade tenderization - Hajmeer, M.N.; Ceylan, E.; Marsden, James L.; Phebus, Randall K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The effect of blade tenderization on translocation of natural microflora from the surface to the interior of longissimus dorsi steaks aged for 7, 14, and 21 days was evaluated. Samples from the exterior and interior of steaks from blade-tenderized (BT) and non-blade-tenderized (N-BT) strip loins were analyzed for aerobic plate, coliform, and Escherichia coli counts. Results showed that BT translocated microorganisms (aerobic plate counts) from the exterior to the interior of muscle. Microorganism numbers increased with extended storage (P<.05). Counts of coliforms and Escherichia coli recovered from BT steaks were comparable to those from N-BT steaks because of very low exterior counts, showing the importance of good hygiene.
Keywords: Beef; Blade tenderization; Beef steaks; Microflora translocation